2021
DOI: 10.3390/jcdd8040040
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of the Cardiac Pacemaking Complex: Electrogenic Principles of Sinoatrial Node Morphogenesis

Abstract: Cardiac pacemaker cells located in the sinoatrial node initiate the electrical impulses that drive rhythmic contraction of the heart. The sinoatrial node accounts for only a small proportion of the total mass of the heart yet must produce a stimulus of sufficient strength to stimulate the entire volume of downstream cardiac tissue. This requires balancing a delicate set of electrical interactions both within the sinoatrial node and with the downstream working myocardium. Understanding the fundamental features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 166 publications
1
24
0
Order By: Relevance
“…Consistent with our findings, TGFβ/BMP signaling mediators have been found enriched in the embryonic SAN (Vedantham et al, 2015;van Eif et al, 2019;Goodyer et al, 2019), which is maintained in adulthood (Linscheid et al, 2019;Brennan et al, 2020). Even though the exact role of TGFβ/BMP signaling during SAN development is not known, it has been proposed to be involved in recruitment of proepicardial cells and remodeling of interstitium in the SAN niche (Easterling et al, 2021). Comparably, WNT signaling has been described as a critical cue for SAN development (Bressan et al, 2013;Ren et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our findings, TGFβ/BMP signaling mediators have been found enriched in the embryonic SAN (Vedantham et al, 2015;van Eif et al, 2019;Goodyer et al, 2019), which is maintained in adulthood (Linscheid et al, 2019;Brennan et al, 2020). Even though the exact role of TGFβ/BMP signaling during SAN development is not known, it has been proposed to be involved in recruitment of proepicardial cells and remodeling of interstitium in the SAN niche (Easterling et al, 2021). Comparably, WNT signaling has been described as a critical cue for SAN development (Bressan et al, 2013;Ren et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…TGFB and BMP2 are reportedly involved in formation of the SAN (Easterling et al, 2021). We found that several TGFB L-R interactions affect SAN CM specifically, as well as BMP2 and BMP4.…”
Section: Resultsmentioning
confidence: 99%
“…As there were too few SAN CMs to identify by the clustering algorithm, they were detected using a supervised approach as cells coexpressing TBX18, SHOX2 , and HCN4 (Easterling et al, 2021; Liang et al, 2017; Wiese et al, 2009). In the map generated by UMAP analysis (Figure 2A), showing the two atrial clusters (clusters 3 and 5), SAN CMs are located at the upper end of atrial cluster 5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, dissociated cells of many organs show high heterogeneity of their oscillations. Isolated individual sinoatrial node cardiac pacemaker cells have varying periods [66][67][68][69], but at high density, they exhibit the stereotypical 80 beats per minute [61,70]. Dispersed cultures of suprachiasmatic nucleus (SCN) neurons behave as non-synchronous singlecell oscillators and fire with widely varying circadian periods distinct from 24 h [71,72].…”
Section: The Impact Of Entrainment On Heterogeneity Between Individua...mentioning
confidence: 99%